1993
DOI: 10.1002/crat.2170280515
|View full text |Cite
|
Sign up to set email alerts
|

Role of Silver on Superconducting Properties of BPSCCO (2223) System

Abstract: The role of silver for the superconducting properties of the Bi -Pb -Sr -Ca -Cu-0 (2223) system have been investigated systematically. Samples with various concentrations of Ag were prepared by the matrix method. D.C. resistance results showed that TJO) varied between 100-109 K for various compositions of Ag. J , measured at LNT from I-V data shows an increase with silver addition. J , decreased from 90 Amp/cmz at zero field to 16 Amp/cmz at 100 Oe. The r(0) obtained from the susceptibility data agreed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…However, Ag plays the role to promote the growth rate of Bi-2223 phase, as well as to enhance the connectivity of these grains were obtained, which was evidenced by less porosities in A5 sample. The scanning electron micrographs indicated that silver is precipitated along the grain boundaries, separating the superconducting grains [19]. These results have showed that silver addition does not destroy the superconductivity and at the same time enhances the critical current density.…”
Section: Scanning Electron Microscope (Sem) Imagesmentioning
confidence: 69%
“…However, Ag plays the role to promote the growth rate of Bi-2223 phase, as well as to enhance the connectivity of these grains were obtained, which was evidenced by less porosities in A5 sample. The scanning electron micrographs indicated that silver is precipitated along the grain boundaries, separating the superconducting grains [19]. These results have showed that silver addition does not destroy the superconductivity and at the same time enhances the critical current density.…”
Section: Scanning Electron Microscope (Sem) Imagesmentioning
confidence: 69%